The Biblical concept of Shalom in the context of globalization and its consequent ethical implications (Hekima Review, 2006)
One thing we noted was that though everyone said they wanted peace and harmony, unfortunately conflicts grew more acute and threats multiplied. (John XXIII) “We live in a broken world” is the title of a Jesuit study written as a follow up to the Decree on Ecology of the 34th General Congregation.1 This metaphor of brokenness characterizes well the context of the world today, such as the reality of brokenness in Africa that is portrayed in the “Western” media: collapsing states; violent conflicts; natural disasters, and the loss of lives and massive displacements of people within their countries and across borders. Brokenness characterizes the loss of integrity, wholeness or wellbeing; it is also the experience of all immigrants whether in Africa, Europe, or America today.